How socioemotional setting modulates late-stage conflict resolution processes in the lateral prefrontal cortex - Schreiter, Marie Luise; Chmielewski, Witold X; Beste, Christian (Cognitive, affective & behavioral neuroscience, 2018)
The goal-directed control of behaviour critically depends on emotional regulation and constitutes the basis of mental well-being and social interactions. Within a socioemotional setting, it is necessary to prioritize effectively the relevant emotional information over interfering irrelevant emotional information to orchestrate cognitive resources and achieve appropriate behavior. Currently, it is elusive whether and how different socioemotional stimulus dimensions modulate cognitive control and conflict resolution. Theoretical considerations suggest that interference effects are less detrimental when conflicting emotional information is presented within a "positive socioemotional setting" compared with a "negative socioemotional setting." Using event-related potentials (ERPs) and source localization methods, we examined the basic system neurophysiological mechanisms and functional neuroanatomical structures associated with interactive effects of different interfering facial, socioemotional stimulus dimensions on conflict resolution. We account for interactive effects of different interfering socioemotional stimulus dimensions on conflict resolution, i.e., we show how the socioemotional valence modulates cognitive control (conflict processing). The data show that conflicts are stronger and more difficult to resolve in a negative emotional task-relevant setting than in a positive emotional task-relevant setting, where incongruent information barely induced conflicts. The degree of emotional conflict critically depends on the contextual emotional valence (positive or negative) in which this conflict occurs. The neurophysiological data show that these modulations were only reflected by late-stage conflict resolution processes associated with the middle (MFG) and superior frontal gyrus (SFG). Attentional selection processes and early-stage conflict monitoring do not seem to be modulated by interactive effects of different interfering socioemotional stimulus dimensions on conflict resolution.
Keywords: EEG; Source localization; Humans; evokované potenciály; mapování mozku; Attention; Faces; výraz obličeje; Emotions; Female; mladý dospělý; dospělí; vyjednávání; lidé; Negotiating; Brain Mapping; Adult; ženské pohlaví; Male; Evoked Potentials; Conflict processing; emoce; Young Adult; mužské pohlaví; Facial Expression; pozornost